The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/om000553i
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Trimethylaluminum with [(tBu)Al(μ3-O)]6:  Hybrid tert-Butylmethylalumoxanes as Cocatalysts for Olefin Polymerization

Abstract: The reaction of trimethylaluminum with the hexameric tert-butylalumoxane, [( t Bu)Al-(µ 3 -O)] 6 , has been investigated. Reaction of [( t Bu)Al(µ 3 -O)] 6 with 1 equiv of AlMe 3 results in the formation of two isomers (A and B) of the hybrid tert-butylmethylalumoxane, [Al 7 (µ 3 -O) 6 -( t Bu) 6 Me 3 ]. The structures of compounds A and B, as determined by NMR spectroscopy and mass spectrometry, consist of [Al 6 (µ 3 -O) 6 ( t Bu) 5 Me] alumoxane cages, formed via tert-butyl/ methyl exchange, in which one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 30 publications
3
61
0
1
Order By: Relevance
“…This was found to give the highest catalytic activity, comparable to that of MAO. [22] All these data are in favor of a three-dimensional cage structure of MAO. On the basis of Barron's studies on tert-butylaluminoxanes, Sinn concluded by means of molar-mass determination and phase separation studies that MAO has an [Al 4 O 3 (CH 3 ) 6 ] structure.…”
Section: Molar Massmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found to give the highest catalytic activity, comparable to that of MAO. [22] All these data are in favor of a three-dimensional cage structure of MAO. On the basis of Barron's studies on tert-butylaluminoxanes, Sinn concluded by means of molar-mass determination and phase separation studies that MAO has an [Al 4 O 3 (CH 3 ) 6 ] structure.…”
Section: Molar Massmentioning
confidence: 99%
“…However, recently, Bochmann and Sarfield [113] found that AlR 3 reacts with [Ph 3 C] + [B(C 6 F 5 ) 4 ] -to give BR 3 and AlR 3-x (C 6 F 5 ) x , a reaction, which is slow if R is Me, but happens instantaneously when R is an isobutyl group. It was also found that Cp 2 ZrMe 2 reacts with Al(C 6 F 5 ) 3 (20) to give unstable Cp 2 ZrMe(l-Me)Al(C 6 F 5 ) 3 (21), which rapidly decomposes to Cp 2 ZrMe(C 6 F 5 ) (22). The significant reduction in activity with time observed with the catalyst combination used by Chien and coworkers may be due to the degradation reactions of B(C 6 F 5 ) 4 -mentioned above.…”
Section: Boron-based Activatorsmentioning
confidence: 99%
“…They considered the TMAseparated ion pair as a real precursor of active centers for olefin polymerization. Recently, Watanabe et al [21] have shown that the reaction between tert-butylaluminoxane [(t-Bu)Al(l 3 -O)] 6 and AlMe 3 produces a new hybrid aluminoxane [Al 7 (t-Bu) 6 (l 3 -O) 6 Me 3 ]. The system [Me 2 C(Cp)(Flu)]Zr(CH 2 C 6 H 5 ) 2 + Al 7 (t-Bu) 6 (l 3 -O) 6 Me 3 is active in 1,5-hexadiene polymerization and its activity increases sharply on the addition of AlMe 3 .…”
Section: Methods and Details Of Calculationsmentioning
confidence: 99%
“…[9] Recently, it was shown that AlMe 3 also reacts with tert-butylaluminoxane by the same reaction (Reaction 1). [21] Models of "true" MAO structures with the composition [(AlMeO) 3m N mAlMe 3 ] (m = 2, 3, 4) have been suggested. [16] A common principle for the design of molecular MAO structures characterized by the ratio Al/ Me/O = 1 : 1.5 : 0.75 has been proposed, [13,16] in which it is suggested that the (AlMeO) 3m N mAlMe 3 structures ("true" MAO) are formed by bonding the mAlMe 3 molecules to the cage structure (AlMeO) 3m ("classic" MAO), with m = 2, 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, only Barron and coworkers have published some chemistry of these compounds: the structural characterization of the corresponding tertbutyl derivatives 2,3 and a new method for the determination of the trialkylaluminum content in aluminoxanes; 4 in addition they described the reactions of trimethylaluminum (Me 3 Al) with tert-butylaluminoxanes 5 and the formation of methylaluminoxane (MAO) in the decomposition reaction of dimethylaluminum alkoxyderivatives. 6 Other studies regarded mostly the chemistry of MAOs, and in particular an approach to their structural elucidation.…”
Section: Introductionmentioning
confidence: 99%